Study of magnetoresistance of epitaxial magnetite films grown on vicinal MgO (100) substrate - SHVETS, IGOR; ARORA, SUNIL (My University, 2005)
The magnetoresistance sMRd studies of magnetite thin films deposited on vicinal MgO substrates show an enhanced MR along the miscut direction as compared to the direction perpendicular to it. The MR anisotropy increases with the decrease in temperature and peaks at the Verwey transition. The increase in magnetoresistance and anisotropy behavior is attributed to the formation of a greater number of out-of-plane shifted antiphase boundaries due to the step edges on vicinal MgO substrates. These local electronic and spin structure modifications at the APBs introduce additional spin scattering and are responsible for the increase in MR along the miscut
PUBLISHED
Keywords: Surface Physics; thin films